MAIN CHALLENGES AND OPPORTUNITIES FACED BY THE NONPROFIT SECTOR IN CURRENT POLAND - Rymsza, Agnieszka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
There are over 100 000 nonprofit organizations registered in Poland that constitute a growingly important actor in the economic area and for the public administration. The sector has been growing, yet there are many factors that distract nonprofit organizations from carrying out many of their missions and goals and from playing many of the important functions in a society that are or were expected from them. This paper presents the main challenges and opportunities faced by the nonprofit sector in Poland in the recent years and at the beginning of 2016 as well as both the negative and positive trends observed in its development. A stress will be put on the relations between nonprofit organizations and the government and the process of governmentalization will be described.